Self-Efficacy and Feeling of Security Associated with Risky Sexual Behavior among Commercial Sex Workers Living with HIV - Anki Tias Yolanda; Agung Waluyo; Lestari Sukmarini (Fakultas Ilmu Keperawatan Universitas Indonesia, 2020)
Commercial sex workers (CSWs) represent a key population for HIV transmission. CSWs continue to thrive because of the development of the tourism sector and the acceptance of communities. This study aimed to identify the factors associated with risky sexual behavior among CSWs living with HIV. A cross-sectional design was adopted. The sample size was set to 80 CSWs living with HIV in the Special Region of Yogyakarta and Central Java. Chi-square and multiple logistic regression were used in the data analysis. Results showed the significant relationship of self-efficacy (p < 0.001; OR = 9.365) and feeling secure (p= 0.033; OR= 2.762) with risky sexual behavior. No significant relationship was noted between income (p= 0.244), knowledge (p= 0.110), attitude (p= 0.978), drug use (p= 0.150), alcohol consumption (p= 0.642), and sexual violence (p= 0.968) and risky sexual behavior. Nursing practices are expected to focus on promotive and preventative efforts by involving communities in enhancing the feeling of security and self-efficacy of CSWs through health programs and improvement of health facilities. Abstrak Efikasi Diri dan Perasaan Aman Berhubungan dengan Perilaku Seksual Berisiko pada Pekerja Seks Komersial dengan HIV. Pekerja Seks Komersial (PSK) menjadi populasi kunci penularan HIV. Perkembangan sektor pariwisata dan penerimaan masyarakat menjadikan PSK tetap bertahan. Penelitian ini bertujuan mengidentifikasi faktor-faktor yang memengaruhi perilaku seksual berisiko pada PSK dengan HIV positif. Desain penelitian ini adalah cross-sectional dengan jumlah sampel 80 Orang Dengan HIV AIDS (ODHA) PSK di Daerah Istimewa Yogyakarta dan Jawa Tengah. Analisis data menggunakan Chi-Square dan regresi logistik ganda. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara efikasi diri (p< 0,001; OR= 9,365) dan perasaan aman (p= 0,033; OR= 2,762) dengan perilaku seksual berisiko. Tidak terdapat hubungan yang signifikan antara penghasilan (p= 0,244), pengetahuan (p= 0,110), sikap (p= 0,978), pemakaian narkoba (p= 0,150), konsumsi alkohol (p= 0,642), dan kekerasan seksual (p= 0,968) dengan perilaku seksual berisiko. Pelayanan keperawatan diharapkan lebih berfokus pada upaya promotif dan preventif dengan melibatkan masyarakat dalam meningkatkan rasa aman dan efikasi diri PSK melalui program-program kesehatan dan peningkatan fasilitas kesehatan. Kata Kunci: HIV, pekerja seks komersial, perilaku seksual berisiko